Investigation of Open Marine Wind Energy Potential by Weibull Distribution and Implementation to Izmir and Antalya - Karakaya, Duygu; Tatlipinar, Hasan (AMER INST PHYSICS, 2018)
Solid and gaseous fuels as an energy sources in the world are both limited and cause significant environmental problems when consumed. For this reason, clean energy production is very important. Solar and wind energy are the main clean energy sources. For the wind energy high efficiency wind turbines are needed. The efficiency of the turbine depends engineering design of the turbine, the material used and the wind potential of the zone. Engineering design and material factors are factors that can improve, but the wind depends entirely on the nature of the region and can't be changed. For this reason, it is important to determine the parameters of the wind potential distribution of the selected region. In this presentation, the wind measurements taken for the 4 month time period covering the winter period of Izmir and Antalya coastal areas were analyzed with help of the Weibull distribution.
Keywords: Physics